Pseudouridine and ribothymidine formation in the tRNA-like domain of turnip yellow mosaic virus RNA. - Becker, H F (1998)
The last 82 nucleotides of the 6.3 kb genomic RNA of plant turnip yellow mosaic virus (TYMV), the so-called 'tRNA-like' domain, presents functional, structural and primary sequence homologies with canonical tRNAs. In particular, one of the stem-loops resembles the TPsi(pseudouridine)-branch of tRNA, except for the presence of a guanosine at position 37 (numbering is from the 3'-end) instead of the classical uridine-55 in tRNA (numbering is from the 5'-end). Both the wild-type TYMV-RNA fragment and a variant, TYMV-mut G37U in which G-37 has been replaced by U-37, have been tested as potential substrates for the yeast tRNA modification enzymes. Results indicate that two modified nucleotides were formed upon incubation of the wild-type TYMV-fragment in a yeast extract: one Psi which formed quantitatively at position 65, and one ribothymidine (T) which formed at low level at position U-38. In the TYMV-mutant G37U, besides the quantitative formation of both Psi-65 and T-38, an additional Psi was detected at position 37. Modified nucleotides Psi-65, T-38 and Psi-37 in TYMV RNA are equivalent to Psi-27, T-54 and Psi-55 in tRNA, respectively. Purified yeast recombinant tRNA:Psisynthases (Pus1 and Pus4), which catalyze respectively the formation of Psi-27 and Psi-55 in yeast tRNAs, are shown to catalyze the quantitative formation of Psi-65 and Psi-37, respectively, in the tRNA-like 3'-domain of mutant TYMV RNA in vitro . These results are discussed in relation to structural elements that are needed by the corresponding enzymes in order to catalyze these post-transcriptional modification reactions.